2007
DOI: 10.1080/13607860601086603
|View full text |Cite
|
Sign up to set email alerts
|

Personality changes in Alzheimer's disease

Abstract: Personality changes have been depicted to be influenced by severity of cognitive, functional and behavioural complaints rather than age, sex, education and disease duration. These first applications of the Italian version of PI confirmed that personality modifications make a consistent aspect of the phenomenology of AD although in the negative direction. Further studies are needed to understand the nature of personality changes in dementia and the utility of PI to investigate these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
0
19
1
3
Order By: Relevance
“…Overall, there seems to be a predictable increase in neuroticism and a decrease in extraversion, conscientiousness and possibly openness to experience in MCI patients compared to control subjects. This change is in contrast with the overall stability of personality traits observed in control subjects [37], in whom modifications occur, if at all, slowly and imperceptibly [47], but never as quickly and profoundly as observed in our clinical group. In keeping with the findings of our study, Siegler et al [48] found that patients diagnosed with memory impairment had higher values in neuroticism and lower ones in openness, extraversion and conscientiousness.…”
Section: Discussioncontrasting
confidence: 53%
“…Overall, there seems to be a predictable increase in neuroticism and a decrease in extraversion, conscientiousness and possibly openness to experience in MCI patients compared to control subjects. This change is in contrast with the overall stability of personality traits observed in control subjects [37], in whom modifications occur, if at all, slowly and imperceptibly [47], but never as quickly and profoundly as observed in our clinical group. In keeping with the findings of our study, Siegler et al [48] found that patients diagnosed with memory impairment had higher values in neuroticism and lower ones in openness, extraversion and conscientiousness.…”
Section: Discussioncontrasting
confidence: 53%
“…The Previous research has demonstrated that patients in different stages of AD display an increase in neuroticism and a decrease in extraversion, openness, conscientiousness, and agreeableness in relation to normal elderly [8][9][10] . A recent study has reported patients being quieter, relying on others, disliking of company, unhappy and regressive after onset of AD, when compared to healthy control subjects [11] . Patients with AD furthermore express more apathy, increased rigidity and less interest in hobbies.…”
mentioning
confidence: 99%
“…ISSN: 0214-9877. pp:177-186 183 con su alrededor, indiferencia con sus actividades y tareas, y con menor probabilidades de percibir estímulos de bajos niveles de intensidad. (Boyle, Wilson, Schneider, Bienias & Bennett, 2008;Duberstein et al, 2011;Evans & Rothbart, 2007;Hertzog, Kramer, Wilson & Lindenberger, 2009;Talassi, Cipriani, Bianchetti & Trabucchi, 2007;Tucker-Drob, Johnson & Jones, 2009). La responsabilidad, por su turno, cuando se presenta con niveles bajos y expresión negativa, caracteriza al mayor por su desorganización, desinterés por su trabajo y incapacidad de planificar acciones.…”
Section: Discussionunclassified